Fluoroscopy guided ventriculo-atrial shunt insertion - Ernesto Enrique Horta-Tamayo; Luis Cesar Acosta-González; Carlos García-Alonso; Enrique Antonio González-Hernández (Gaceta Médica Espirituana)
Background: The ventriculo-atrial shunt is performed routinely for the treatment of hydrocephalus when the ventriculo-peritoneal shunt has failed or patients present some intra-abdominal disease that contraindicates the peritoneum as an ideal destination. During surgery, placing the distal end of the catheter at the cavo-atrial junction is essential for preventing possible complications.